2017
DOI: 10.1089/neu.2015.4333
|View full text |Cite
|
Sign up to set email alerts
|

Increases of Plasma Levels of Glial Fibrillary Acidic Protein, Tau, and Amyloid β up to 90 Days after Traumatic Brain Injury

Abstract: Glial fibrillary acidic protein (GFAP), microtubule-associated protein tau, and amyloid b peptide (Ab42) have been proposed as diagnostic and prognostic biomarkers in traumatic brain injury (TBI). Single molecule array (Simoa) is a novel technology that employs highly sensitive immunoassays for accurate measurements of candidate biomarkers found at low concentration in biological fluids. Our objective was to trace the trajectory of tau, GFAP, and Ab42 levels in plasma from the acute through subacute stages aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 47 publications
(66 reference statements)
8
126
0
Order By: Relevance
“…The discrepancy between the current studies' findings and those of Nesilus and colleagues are unclear, warranting future research on the potential dysregulation of plasma T-tau chronically after brain injury. Understanding the relationship between peripheral blood T-tau levels and axonal injury or the accumulation of tau in the brain is important, as peripheral tau has been linked to chronic neurodegenerative disorders such as chronic traumatic encephalopathy and Alzheimer's disease (42,47,(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the current studies' findings and those of Nesilus and colleagues are unclear, warranting future research on the potential dysregulation of plasma T-tau chronically after brain injury. Understanding the relationship between peripheral blood T-tau levels and axonal injury or the accumulation of tau in the brain is important, as peripheral tau has been linked to chronic neurodegenerative disorders such as chronic traumatic encephalopathy and Alzheimer's disease (42,47,(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…GFAP levels in CNS have been suggested to improve TBI outcome prediction models and may be able to serve as a marker of intracranial injury (67,68). In fact, GFAP in CSF has been reported to have higher diagnostic accuracy than S100B (69) and was recently shown to have excellent accuracy in differentiating mTBI patients from controls (70). While the best candidate biomarker for mTBI remains to be determined, GFAP does have this clear advantage over S100B.…”
Section: Biomarkers Of Traumatic Neuronal/axonal Injurymentioning
confidence: 99%
“…For example, plasma tau is measurable by Simoa, which showed an increase of the protein in hockey players after concussion and in military personnel who sustained TBIs [74]. A recent study using Simoa showed increases in plasma tau and Aβ42 levels even up to 90 days after mild and moderate-to-severe TBI [75]. …”
Section: Development Of Biomarker Assays From Body Fluidsmentioning
confidence: 99%